The Cornerstones of Engaging Leadership (with CD) - Wilson, Casey (Berrett-Koehler Publishers, 2008)
In the 21st Century, people are the competitive advantage. The talent and level of dedication of an organization's workforce make the difference in achieving success. The traditional command-oriented leadership style is not enough to keep today's employees motivated--they need to be engaged. They need passion, connection, and inspiration, and a willingness to put forth their best efforts to benefit themselves and their organization. The Cornerstones of Engaging Leadership connects what we know about engagement on an organizational level to what an individual leader can do to increase engagement. Using real-world examples, Wilson reveals the key actions leaders must take to connect with and engage others: " uild trust " everage unique motivators " anage performance from a people-centric perspective " ngage emotions By committing to these four cornerstones of engaging leadership, leaders can unleash the potential of others and inspire effective performance. Through practice tools and exercises (all available for download on a supplemental CD-ROM), readers are challenged to explore, reflect upon, and apply key concepts and techniques of the engaging leader approach